2019
DOI: 10.1002/anie.201905274
|View full text |Cite
|
Sign up to set email alerts
|

Dimension‐Matched Zinc Phthalocyanine/BiVO4 Ultrathin Nanocomposites for CO2 Reduction as Efficient Wide‐Visible‐Light‐Driven Photocatalysts via a Cascade Charge Transfer

Abstract: Die rationale Entwicklung effizienter Photokatalysatoren mit günstiger Ladungstrennung und breiter spektraler Absorption ist entscheidend für eine ökonomische Umwandlung von Solarenergie in chemische Energie. F. Q. Bai, J. Tang, L. Q. Jing et al. zeigen in ihrer Zuschrift auf S. 10989 H‐verbrückte ZnPc/BiVO4‐Nanokomposite als ultradünnen, räumlich angepassten 2D/2D‐Heteroübergang zur effizienten photokatalytischen CO2‐Reduktion über eine breite Region des sichtbaren Lichts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
69
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(71 citation statements)
references
References 34 publications
2
69
0
Order By: Relevance
“…In contrast, under the same illumination conditions, BiOCl has the lowest emission intensity owning to the low intrinsic photoresponse of BiOCl . Furthermore, it's carefully observed that the PL emission intensity of the as‐prepared samples were declined with increasing the content of BiOCl, suggesting that the photoinduced electrons transformation direction is from CN to BiOCl …”
Section: Resultssupporting
confidence: 82%
“…In contrast, under the same illumination conditions, BiOCl has the lowest emission intensity owning to the low intrinsic photoresponse of BiOCl . Furthermore, it's carefully observed that the PL emission intensity of the as‐prepared samples were declined with increasing the content of BiOCl, suggesting that the photoinduced electrons transformation direction is from CN to BiOCl …”
Section: Resultssupporting
confidence: 82%
“…[ 27–30 ] BiVO 4 has exhibited excellent photocatalytic activities by its unique intrinsic properties, such as in photocatalytic CO 2 reduction. [ 31–33 ] Furthermore, Majima and co‐workers has certificated the feasibility of BiVO 4 in H 2 ‐evolution through constructing 2D heterostructure with BP. [ 34 ] However, the studies of BiVO 4 ‐based materials in H 2 ‐evolution are extremely rare, [ 35,36 ] which is indeed worth of more extensive research.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have made early attempts to fabricate a PEC‐PV solar water splitting device, for example, a BiVO 4 –silicon cell, WO 3 /Fe 2 O 3 ‐dye sensitized solar cell, and more recently, a nanocone BiVO 4 ‐perovskite tandem cell . For the PEC part, BiVO 4 has been intensively studied as a photoanode with a suitable band gap to harvest a substantial amount of sunlight as well as a suitable band edge position to straddle the redox potentials of the oxygen evolution reactions . The relatively small onset potential for oxygen evolution reaction (OER) on the BiVO 4 photoanode would yield a sufficiently high current density at a suitable bias that can match with the maximum power point of a photovoltaic cell to design efficient tandem devices.…”
Section: Introductionmentioning
confidence: 99%